TVET delivery : providing innovative solutions - Keevy, James [Verfasser]; Shiohira, Kelly [Verfasser] (UNESCO-UNEVOC International Centre for Technical and Vocational Education and Training, 2021)
This volume focuses on the micro-level stakeholders involved in the implementation of TVET skilling programmes and/or their components. It will suit lecturers, administrators and programme designers interested in understanding some of the challenges and opportunities of introducing new qualifications and competencies into TVET programmes. The volume aims to address the role and contributions of TVET providers and companies in identifying, integrating and implementing new qualifications and competencies, drawing on contributions from literature as well as expert engagements and case studies. Readers are encouraged to explore the other two volumes for additional insights: ‘TVET advocacy: ensuring multistakeholder participation’ targets the meso level, and ‘TVET governance: steering collective action’ focuses on macro-level stakeholders. (Publisher's abstract ; BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; S 3.2 Unternehmen und Behörden; S 3.1.2.1 Berufliche Teilzeitschulen, Berufsschulen; 370; 330; Berufsbildung; Internationale Zusammenarbeit; Bildungsträger; Ausbildungsstätte; Ausbildungsbetrieb; Berufsschule